PENGARUH KEUNTUNGAN RELATIF, FITUR LAYANAN, RISIKO, DAN KEPATUHAN SYARIAH TERHADAP MINAT TRANSAKSI MENGGUNAKAN BSI MOBILE DI KOTA BANDA ACEH - Astuti, Cindy; Saputra, Mulia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to see and analyze the effects of relative advantage, service features, risk, and shariah compliance on interesting transactions of the customers that use BSI mobile. The object of this study is Bank Syariah Indonesia customers in Banda Aceh city who use BSI mobile. Samples were taken by purposive sampling method. There are 100 samples of the data which became the object to be researched. This research is quantitative research with primarily data obtained by distributing questionnaires of interviews. The results show that relative advantages, service features, risk and sharia compliance give an effect to the user of BSI mobile simultaneously. The results of this research also show and give positive effects and are significant for the customers interest in using BSI mobile, whereas the risk dont give effects for the customers interest in using BSI mobile.